FASD: The Living Experience of People with Fetal Alcohol Spectrum Disorder—Results of an Anonymous Survey - Emily Hargrove; C. J. Lutke; Katrina Griffin; Myles Himmelreich; Justin Mitchell; Anique Lutke; Peter Choate (Disabilities, 2024)
Fetal Alcohol Spectrum Disorder (FASD) is considered a lifelong disability that has been framed with neurobiological descriptions focused on the brain. These are important features but fail to tell the story of living with FASD. By surveying those with FASD, this work expanded upon prior survey work which illustrated a multitude of early-onset physiological issues occurring at rates much higher than is typical of the general population. The current project, again using an anonymous survey methodology, sought to open up other direct experiences to better understand the complexity of living with FASD. An anonymous online survey was used to gather data on adversity in childhood, schooling, employment, housing and finances, and involvement with the criminal justice system, as well as relationships and parenting. Results indicate high levels of adversity throughout the life span; vulnerability to manipulation, which is connected to involvement in the criminal justice system; struggles with housing; economic instability; and struggles maintaining employment, as well as difficulties with social and familial relationships. Systemic stigma was also identified. Suggestions are offered to inform others on how support can be enhanced and targeted with a goal of improving quality of life, as well as dealing with self-imposed stigma. The survey was developed by adults living with FASD who have served as a long-standing advocacy and educational group influencing policy and practice in the field.